Implementation of Pancasila education learning through an ethnopedagogical-based cooperative learning approach using Canva media - Feri Tirtoni; Qurota A'yun; Siti Nadhiyatul Wijayanti; Ikalimanda Putri Yuanaantari; Farhan Febryan (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This article discusses the implementation of Pancasila Education at SD Muhammadiyah 2 Krian, using an ethnopedagogic-based cooperative learning approach combined with Canva as a digital tool. The goal is to develop students' character in faith, independence, mutual cooperation, diversity, critical thinking, and creativity. Canva’s interactive features enhance student creativity, motivation, and understanding of Pancasila values in a contextual and engaging way. The research shows this method effectively improves student involvement and social skills. However, challenges such as limited digital infrastructure in remote areas and varying understanding of Pancasila remain. To address these challenges, regular teacher training, adaptive curricula, and support from the government, schools, and communities are necessary. This holistic support is crucial to ensure the sustainable and relevant implementation of Pancasila Education in the digital era. The combination of cooperative learning and digital media helps students apply national values in everyday life while preserving local cultural identity.